2014
DOI: 10.1111/srt.12156
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of two in vivo measurements for skin surface topography in aged adults

Abstract: The Visioscan® parameters SEr, Rmax, and Rz showed most reliable and valid values and were largely comparable on contralateral forearm skin sites in elderly subjects. Rmax, Rz, and Ra should be preferred for measuring skin surface topography with PRIMOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 24 publications
(31 reference statements)
3
35
0
Order By: Relevance
“…22,23 Roughness measurements were conducted in a controlled room temperature of 22 AE 2°C and 50% AE 10% relative humidity and after the participants' acclimatization for at least 30 min. The Visioscan® VC 98 camera and the corresponding software SELS 2000 (both Courage & Khazaka Electronic GmbH, Cologne, Germany) were used to measure the DIN/ISO parameters R z (arithmetic mean roughness from five consecutive sampling lengths) and R max (maximal roughness).…”
Section: Criterion Validation Of the Item "Surfacementioning
confidence: 99%
“…22,23 Roughness measurements were conducted in a controlled room temperature of 22 AE 2°C and 50% AE 10% relative humidity and after the participants' acclimatization for at least 30 min. The Visioscan® VC 98 camera and the corresponding software SELS 2000 (both Courage & Khazaka Electronic GmbH, Cologne, Germany) were used to measure the DIN/ISO parameters R z (arithmetic mean roughness from five consecutive sampling lengths) and R max (maximal roughness).…”
Section: Criterion Validation Of the Item "Surfacementioning
confidence: 99%
“…We have used the DIN/ISO parameters R max⁡ and R z because previous studies showed that these are the parameters with high reliability and validity estimates in elderly subjects [32]. While R max⁡ represents the maximal roughness, R z is defined as the arithmetic mean roughness from five consecutive sampling lengths.…”
Section: Methodsmentioning
confidence: 99%
“…Attempts have been made to quantify measurements with ever increasing precision using imaging techniques. High-resolution ultrasound (e.g., PRIMOS) [25] has been directed to reveal minute changes in skin surface texture. Magnetic resonance imaging, similarly, has been analyzed to specify the volumetric fat reduction resulting from noninvasive procedures [26].…”
Section: Subjectivity Of Outcome Measuresmentioning
confidence: 99%